Terawatt Solar Photovoltaics Roadblocks and Opportunities - Tao, Meng. (SpringerBriefs in Applied Sciences and Technology,, 2014)
Solar energy will undoubtedly become a main source of energy in our life by the end of this century, but how big of a role will photovoltaics play in this new energy infrastructure? Besides cost and efficiency, there are other barriers for current solar cell technologies to become a noticeable source of energy in the future. Availability of raw materials, energy input, storage of solar electricity, and recycling of dead modules can all prevent or hinder a tangible impact by solar photovoltaics. This book is intended for readers with minimal technical background and aims to explore not only the fundamentals but also major issues in large-scale deployment of solar photovoltaics. Thought-provoking ideas to overcoming some of the barriers are discussed.